Corporate Social Responsibility PT Bank Pembangunan Daerah Jawa Timur Tbk (Bank Jatim) Surabaya - Setyo Adjie Prabowo; Kalvin Edo Wahyudi (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Bank Pembangunan Daerah Jawa Timur Tbk ("Bank Jatim") is one of the largest Regional Banks whose position occupies the second position, and is expected to bring a positive impact, namely economic benefits in East Java Province. Based on Law Number 40 of 2007 explaining social and environmental responsibility as the company's commitment to participate in sustainable economic development, this study aims to find out about how the implementation of corporate social responsibility (CSR) PT. Bank Pembangunan Daerah Jawa Timur Tbk ("Bank Jatim") in 2021 is carried out, which will be reviewed through four implementation models of George C. Edward III mentioned in Agustiono (2008), namely: Communications, Resources, Dispositions, and Bureucratic Structure. The research method used is qualitative descriptive, with data collection techniques using literature studies, in-depth interviews with resource persons, observation, documentation. The results of the study stated that the implementation of Bank Jatim's CSR implementation on communication indicators, resources, and also bureaucratic structure has run well, while the disposition indicators have also run quite well. Keywords: Corporate Social Resposibility (CSR), Bank Jatim, Implementation, Community